Utilizing Product Context Information to Develop New Digital Services in the Construction Industry. - Hille, Matthias (14. Internationale Tagung Wirtschaftsinformatik, 2019)
The construction industry has suffered a decline in productivity for the last decades, among others because of management, connection and planning issues. Although most stakeholders in construction are aware of the benefits offered by digitalisation in other sectors, the investment in digital solutions is below 1%. The core competencies of suppliers are producing and supplying semi-finished products to retailers or other non-end-users. One solution to digitalise suppliers is to use context information of products to be able to establish new services with increased customer benefits and higher possible margins. In this PhD project categorised, by information type, context information and possibilities to gather this information are matched with service modules. This configurator is then used as a Recommender System for faster service development and service creation to establish new service business models of mid-tier construction suppliers. Mid-tier suppliers have lower market entry barriers, more transparency and new business models when using the system.<br
Keywords: Context information; construction industry; information generation; business model recommendation; service business